Students' Mathematical Communication Ability In View From The Numbered Heads Together (NHT) Cooperative Learning Model Using The Open Ended Approach - Hadi, Heri Sopian; Faturyani, Faturyani; Marlina, Marlina; Patty, Elyakim Nova Supriyedi; Iriyani, Sri Astuti (Jurnal Simki Pedagogia, 2023)
Problem learning mathematics at MTs NW Karang Bata is that it still uses a conventional learning model where the teacher tells more stories and talks in informing all the facts and concepts of a lesson, the low motivation and mathematical communication of students is caused by the learning techniques used by the teacher because it does not facilitate students more active in accepting the material presented by the teacher, in this case it affects students' mathematical communication abilities, to overcome this problem the Numbered Heads Together (NHT) cooperative learning model with the Open Ended approach is used. The purpose of this study was to find out the effect of the Numbered Heads Together (NHT) cooperative learning model with an open ended approach on students' mathematical communication skills. This research is an experimental research with a post-test only control group design, which aims to determine the cooperative learning model of the Numbered Heads Together (NHT) type with the Open Ended approach to the mathematical communication skills of class VIII students at MTs NW Karang Bata with a total of 38 students. sampling using random cluster technique, with VIIIA as the experimental class and class VIIIB as the control class. The independent variable in this study is the Numbered Heads Together (NHT) cooperative learning model with the Open Ended approach and the dependent variable is students' mathematical communication skills. Data on student learning outcomes were analyzed using the Polled Variance t test. At a significant level of 5% and obtained T count > T table = t2.543 > t1.690, then accepted and rejected. From the results of the analysis it can be concluded that there is an influence of the Numbered Heads Together (NHT) type cooperative learning model with the Open Ended approach to the mathematical communication skills of class VIII students of MTs.